2011
DOI: 10.1093/bja/aer116
|View full text |Cite
|
Sign up to set email alerts
|

Persistent postoperative pain: where are we now?

Abstract: There has been considerable interest and controversy around persistent postoperative pain for several years. Most of the available data arise from studies with methodological problems (especially its definition in terms of duration, severity, and effect on quality of life and function); however, more recent investigations have begun to address these issues. Although the quoted incidence varies considerably, analysis of the most conservative data shows that there is no doubt that persistent postoperative pain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 39 publications
0
70
0
4
Order By: Relevance
“…Numerous studies have shown that high levels of acute pain following surgery increase the risk of persistent pain as well as a number of other adverse outcomes. [2][3][4][5][6] However, the effect of high pain levels in the period following discharge has not been well researched. 5,20 The few studies conducted in this area, which have reviewed patients following orthopaedic surgery, have shown an association between high pain levels following discharge and the development of PPP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that high levels of acute pain following surgery increase the risk of persistent pain as well as a number of other adverse outcomes. [2][3][4][5][6] However, the effect of high pain levels in the period following discharge has not been well researched. 5,20 The few studies conducted in this area, which have reviewed patients following orthopaedic surgery, have shown an association between high pain levels following discharge and the development of PPP.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6] However, the effect of high pain levels in the period following discharge has not been well researched. 5,20 The few studies conducted in this area, which have reviewed patients following orthopaedic surgery, have shown an association between high pain levels following discharge and the development of PPP. 18,[21][22][23] The high prevalence of moderate-severe pain found in this study could detrimentally affect the patient in both the immediate and longer term.…”
Section: Resultsmentioning
confidence: 99%
“…62,63 The spared nerve injury (SNI) model is typically used to model chronic neuropathic pain, but it can also be used to model persistent postoperative neuropathic pain, since the nerve injury and pain symptoms (hypersensitivity and hyperalgesia) in this model resemble the kind of injury and resulting neuropathic pain that can sometimes occur after intra-operative nerve resections. 62,63 Similar to PI, SNI has also been shown to lead to pain and depression-like behaviors in rats. 17 We have previously shown that systemic infusion of CX546 can relieve both mechanical hypersensitivity and depression-like behaviors in this pain model.…”
Section: Resultsmentioning
confidence: 99%
“…These findings may be in accordance with a recent review that points out that psychosocial factors probably play a role in some situations of persistent postoperative pain, where preoperative pain, severe immediate postoperative pain, and nerve damage are often good predictors. 23 In addition, a recent meta-analysis presented evidence, albeit small, that depression was associated with mortality. 24 The HADS scale score of eight was used in this investigation as a limit for the normal range, although doubts remain as to whether there are safe values to be used as cutoff scores.…”
Section: Discussionmentioning
confidence: 99%